2010
DOI: 10.1590/s0006-87052010000200017
|View full text |Cite
|
Sign up to set email alerts
|

Biomassa de mudas de pepinos híbridos conduzidos sob ambientes protegidos

Abstract: O estudo de oleráceas no Estado de Mato Grosso do Sul, especialmente na região do Pantanal, é fundamental para o desenvolvimento do comércio local e sustentabilidade dos pequenos produtores que circunvizinham as áreas urbanas. Neste contexto, foi desenvolvido experimento com produção de mudas de pepino, estudando o acúmulo de biomassa aérea e radicular dos híbridos Aladdin F1, Nikkey, Safira e Nobre F1, em diferentes ambientes de cultivo e substratos. O experimento foi realizado em 2007, utilizando três ambien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0
3

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
2
6
0
3
Order By: Relevance
“…This happened because the screenhouse did not present LDPF in its coverings, allowing better heat exchange with external environment; it probably enabled the tomato development. Similar results were observed by COSTA et al (2010) In the interactions between cultivation environments and type of tray were verified larger plants in the Sombrite ® , for all types of tray, and higher aerial dry phytomass in the screenhouses (Sombrite ® and Aluminet ® ), for almost all the studied trays (Table 3). COSTA et al (2010) also found higher dry root phytomass in hybrid plants of Nikkey and Safira cucumber (H3) cultivated in screen environments, if compared with greenhouses.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This happened because the screenhouse did not present LDPF in its coverings, allowing better heat exchange with external environment; it probably enabled the tomato development. Similar results were observed by COSTA et al (2010) In the interactions between cultivation environments and type of tray were verified larger plants in the Sombrite ® , for all types of tray, and higher aerial dry phytomass in the screenhouses (Sombrite ® and Aluminet ® ), for almost all the studied trays (Table 3). COSTA et al (2010) also found higher dry root phytomass in hybrid plants of Nikkey and Safira cucumber (H3) cultivated in screen environments, if compared with greenhouses.…”
Section: Resultssupporting
confidence: 86%
“…Similar results were observed by COSTA et al (2010) In the interactions between cultivation environments and type of tray were verified larger plants in the Sombrite ® , for all types of tray, and higher aerial dry phytomass in the screenhouses (Sombrite ® and Aluminet ® ), for almost all the studied trays (Table 3). COSTA et al (2010) also found higher dry root phytomass in hybrid plants of Nikkey and Safira cucumber (H3) cultivated in screen environments, if compared with greenhouses. In this study, the screen environments (Sombrite ® and Aluminet ® ) allowed the rainwater entrance, what probably accelerated the organic matter degradation of the Organosuper ® and provided larger quantity of nutrients for the plants, possibly by the pH reduction (VALENTE et al, 2009).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…However this environment showed less net energy for growth and development of the crop. Interactions between greenhouse environments, substrates types and different cucumber hybrids were evaluated by Costa et al (2010) and verified different behavior of the substrates in the different environments studied, noting that the seedling growth was affected by the environments and the substrates. Response of cucumber hybrids in terms of seedlings dry biomass depended on the substrate and the growing environment.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of that, for papaya seedlings grown in the same recipient, Costa et al (2010c) verified greater height (27.64 cm) in the thermo-reflecting screen in comparison with those in the black screen (23.96 cm). Costa et al (2010b) observed that, for cucumber seedlings, substrates containing soil and coconut fiber provided greater biomass accumulation in the greenhouse and nursery equipped with black screen in relation to thermo-reflecting screen. It can be noted the reciprocal interaction and influence of environments and substrates in the development of various species, where the factors altogether can induce better environmental, physical, and nutritional conditions.…”
mentioning
confidence: 95%